Assessing green technology indicators for cleaner production and sustainable investments in a developing country context. (1st November 2021) - Ikram, Muhammad; Ferasso, Marcos; Sroufe, Robert; Zhang, Qingyu
Abstract: The United Nations proposed the Sustainable Development Goals (SDGs) to foster sustainable development, including tackling environmental challenges and adopting cleaner production practices worldwide. Green technology is crucial for the implementation of the SDGs. Currently, there is an urgent need to form a long-term sustainable investment mechanism for screening, evaluation, and promotion of appropriate green technology. Therefore, this study develops an integrated green technology framework to fill a gap in the literature by prioritizing green technologies' most critical attributes in Pakistan. Initially, we focus on eight leading green technology indicators: Environmental Quality, Resource Utilization, Agriculture & forestry, Green building, Energy utilization, Green Transport, Life Health, and Ecology Safety with the help of the fuzzy Delphi method. Fuzzy Analytical Hierarchy Process (FAHP) is employed to find primary and sub-indicators relative importance. Results reveal that Energy Utilization and agriculture & forestry are significant indicators. Supply chain and sustainable food security, Energy Recycling and Eco-Farming obtained the highest weight scores and are seen as essential among 43 sub-criteria. This study is among the first to assess the green technology indicators for cleaner production and sustainable investment to achieve sustainable development. This study's outcomes can help scholars, managers, government agencies, and decision-makers understand the importance of green technologies to achieve SDGs while simultaneously improving sustainability practices.